In vitro Micropropagation and Pharmacognostical studies in Datura inoxia Mill. - Sangekar, Sarika; Devarkar, Vinod; Pandhure, Narayan (Plantae Scientia, 2019)
Datura inoxia (Family- Solanaceae) is a non-traditional medicinal plant. Datura inoxia has many medicinal properties like anodyne, antispasmodic, hallucinogenic, hypnotic and narcotic etc. Datura inoxia used in the treatment of insanity, fevers with catarrh, diarrhoea, scabies, piles, ulcers, colds, asthma, Cardiac disorders, Impotency, Antispasmodic, Malaria, Baldness and skin diseases. The plant contains several alkaloids, the most active of which is scopolamine. It is also useful in respiratory ailments, rheumatism, elephantiasis, insanity, earache and eye diseases. During the efforts of the present investigation have been made to establish a protocol for in vitro propagation and Pharmacognostic screening of this important medicinal plant.